Squeeze-film hydrogel deposition and dry micropatterning - Ding, Zhenweng; Wan Salim, Wan Wardatul Amani; Ziaie, Babak (ACS Publications, 2010)
In this technical note, we demonstrate a squeeze-film based spacer-free method for creating controllable submicrometer hydrogel films on planar substrates that can be used to photolithographically fabricate hydrogel microstructures. This new technique improves the photolithographic resolution and yield by providing a uniform and low-defect hydrogel film. The optimum polymerization initiation time for achieving such a layer was determined to be around 1 min. For patterning, the dried hydrogel film was coated with a parylene-C masking layer. Subsequent etching in oxygen plasma was used to transfer selected patterns of hydrogel to the substrate in a batch scale.